Collective pharmaceutical procurement in China may have unintended consequences in supply and pricing - Jiang, Shan; Chen, Zhuo; Wu, Tao; Wang, Hui (2020)
The collective pharmaceutical procurement was launched in China in 2018 to reduce the prices of selected drugs, by pooling the demands of member cities and granting the contract to the manufacturer with the lowest bid. We found the procurement significantly decreased the prices of most drugs. We also identified significant price increases on some drugs, indicating that manufacturers of these drugs may have strong market power to manipulate prices. The “winner-takes-all” principle applied in the procurement may further increase the market power of winning manufacturers by expanding their respective market shares. They may take the advantage of the market power to increase drug prices in the long-run. The continuously lowering price-caps may force the losing bidders to exit the market. A careful assessment of the unintended consequences of the collective procurement is warranted.